Linguistic Devices Reflecting Women's Inferiority in Tohari's 'Ronggeng Dukuh Paruk' - Chusni Hadiati (Lensa: Kajian Kebahasaan, Kesusastraan, dan Budaya, 2017)
Inferiority is a state in which one part is lower than another. It is deliberately found in our society which consists of female and male because language choices reflect it. Utterances produced by female and male speaker carry both superiority and inferiority. In some speech communities, women’s language undoubtedly reflects their inferiority. Linguistics offers devices to support the above mentioned phenomena. Literary works provide data for linguistic investigation. A novel by Ahmad Tohari, Ronggeng Dukuh Paruk, shows a social praxis. Applying traditional setting, Tohari describes how women’s speech is portrayed. Rongggeng DukuhParuk is Tohari’s masterpiece which tells the life of a traditional dancer. The utterance produced by female characters indicates their lack of self-esteem. Using qualitative data analysis and contextual pragmatics, this article proves women’s inferiority through linguistic devices. Linguistic devices to show women’s inferiority as they are found in Ronggeng Dukuh Paruk are as follows; (1) question tag, (2) hedging, (3) pragmatic particle, (4) conversational implicature, and (5) metaphor.